Analysis of skiers´ performance using GPS - Gomez-Lopez, P. J.; Hernán, O.; Ramirez, J. V. (Science and Skiing IV, 2009)
INTRODUCTION: Alpine skiing needs tools that enable it to be evaluated in situ. GPS (Global Positional System) provides Information of performance in real time that can be recorded for subsequent analysis. It has been used in alpine skiing on several occasions (Limpach & Skaloud, 2003; Ducret, S. et al., 2006). This study sets out extremely useful data for trainers obtained by using GPS in the control of skiers' training.